2022
DOI: 10.1101/2022.10.25.513667
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ribozyme-phenotype coupling in peptide-based coacervate protocells

Abstract: Condensed coacervate phases are now understood to be important features of modern cell biology, as well as valuable protocellular models in origin of life studies and synthetic biology. In each of these fields, the development of model systems with varied and tuneable material properties is of great importance for replicating properties of life. Here, we develop a ligase ribozyme system capable of concatenating short RNA fragments into extremely long chains. Our results show that formation of coacervate microd… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 69 publications
0
9
0
Order By: Relevance
“…However, for larger 𝐾 𝑃 (𝐾 𝑃 > 30), the reaction in the dense phase starts to determine the overall reactions (Supplementary Figure 15), as under these conditions the majority of the reactant mass is in the dense phase and the majority of T is formed there. By inhibiting transfer between the phases for individual components (Supplementary Figure 16- 22), we were able to find that transfer of ABT from the dense to the dilute phase is critical to obtain the contributions in Figure 3c. Formation of ABT is the most unfavorable step, as it is the step with the highest molecularity.…”
Section: Self-replication Rate Can Be Increased In Coacervatesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, for larger 𝐾 𝑃 (𝐾 𝑃 > 30), the reaction in the dense phase starts to determine the overall reactions (Supplementary Figure 15), as under these conditions the majority of the reactant mass is in the dense phase and the majority of T is formed there. By inhibiting transfer between the phases for individual components (Supplementary Figure 16- 22), we were able to find that transfer of ABT from the dense to the dilute phase is critical to obtain the contributions in Figure 3c. Formation of ABT is the most unfavorable step, as it is the step with the highest molecularity.…”
Section: Self-replication Rate Can Be Increased In Coacervatesmentioning
confidence: 99%
“…The functioning of self-replicators inside coacervate protocells has recently received a lot of attention. Several self-replicating DNA and ribozyme systems have been shown to function inside coacervates, 22,25,62 and in some cases the replication rate is even enhanced. 13 How well self-replication works is highly dependent on the nature of the coacervate material.…”
Section: Self-replication Rate Can Be Increased In Coacervatesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Schoenmakers et al created in vitro biomolecular coacervates with specific compositions of proteins and NAs capable of performing both transcription and translation [96]. Le Vay et al found that, within droplets formed from coacervation of ribozymes (an RNA enzyme) and PLL, the ribozymes displayed an enhanced catalytic rate and yield [97], and further that droplets containing active ribozymes displayed different physical properties (e.g. in droplet growth and adhesion) than those containing inactive ribozymes.…”
Section: Encapsulating Biochemical Reactionsmentioning
confidence: 99%
“…Uptake of the ribozyme and its substrate(s) can be achieved by partitioning into preformed coacervates, 17,19,22,23 or by condensation of the ribozyme and substrate with cationic peptides into RNA-based coacervates (Figure 4.b). 20,21,50 The selected compartmentalization strategy has implications for the local concentration of ribozymes and their substrates: partitioning yields a local concentration of HH-ribozyme of 50 μM (K p = 9600), 23 whereas condensation is estimated to result in local oligonucleotide concentrations as high as several mM. 48,50 However, despite the increased local concentration, not all studies reported a rate enhancement inside coacervates.…”
Section: Concentrating Ribozymes and Substratesmentioning
confidence: 99%